2012
DOI: 10.1002/jmri.23865
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary vein morphology by free‐breathing whole heart magnetic resonance imaging at 3 tesla versus breathhold multi‐detector computed tomography

Abstract: Purpose This study compares pulmonary vein and left atrial anatomy using 3D free-breathing whole-heart magnetic resonance imaging (MR) at 3T and multi-detector computed tomography (MDCT). Materials and Methods Thirty three subjects (19 male, age 49±12 years) underwent free-breathing 3T MR and contrast-enhanced MDCT during inspiratory breath hold. Pulmonary vein parameters (ostial areas, diameters, angles) were measured. Results All pulmonary veins and anomalies were identified by 3T MR and by MDCT. The rig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 50 publications
(58 reference statements)
0
6
0
2
Order By: Relevance
“…Although still practical, the overall mean acquisition time for this 3D respiratory and ECG gated MRA sequence of 7:51 ± 2:58 minutes is longer than acquisition times reported for commonly employed contrast enhanced MRA in expiratory breath hold, without ECG gating (5:45 ± 1:53 minutes) [ 13 ]. Furthermore, although the acquisition window is usually shorter for end-systolic compared to mid-diastolic imaging, mean acquisition time in this study was shorter than that reported in two smaller studies of 3D respiratory and ECG gated MRA of pulmonary veins where mid-diastolic ECG gating was used [ 13 , 16 ]. This increase in acquisition times compared to breath held, ungated MRAs may, in part, be offset by reductions in cardiac motion artifact associated through ECG gating and higher spatial resolution.…”
Section: Discussionmentioning
confidence: 74%
See 3 more Smart Citations
“…Although still practical, the overall mean acquisition time for this 3D respiratory and ECG gated MRA sequence of 7:51 ± 2:58 minutes is longer than acquisition times reported for commonly employed contrast enhanced MRA in expiratory breath hold, without ECG gating (5:45 ± 1:53 minutes) [ 13 ]. Furthermore, although the acquisition window is usually shorter for end-systolic compared to mid-diastolic imaging, mean acquisition time in this study was shorter than that reported in two smaller studies of 3D respiratory and ECG gated MRA of pulmonary veins where mid-diastolic ECG gating was used [ 13 , 16 ]. This increase in acquisition times compared to breath held, ungated MRAs may, in part, be offset by reductions in cardiac motion artifact associated through ECG gating and higher spatial resolution.…”
Section: Discussionmentioning
confidence: 74%
“…Furthermore, although the acquisition window is usually shorter for end-systolic compared to mid-diastolic imaging, mean acquisition time in this study was shorter than that reported in two smaller studies of 3D respiratory and ECG gated MRA of pulmonary veins where mid-diastolic ECG gating was used [13,16]. This increase in acquisition times compared to breath held, ungated MRAs may, in part, be offset by reductions in cardiac motion artifact associated through ECG gating and higher spatial resolution.…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…In general, the anatomical variations of PV ostia were examined in 73 studies including 13,811 subjects (Abadir et al, 2019; Akkaya et al, 2018; Aktan Ikiz et al, 2014; Allgayer et al, 2008; Altinkaynak & Koktener, 2019; Angulo Hervias et al, 2020; Anselme et al, 2006; Anselmino et al, 2011; Artuso et al, 2005; Baszko et al, 2012; Benini et al, 2008; Beukema et al, 2010; Bittner et al, 2011; Boersma et al, 2008; Bogot et al, 2009; Bourier et al, 2013; Brunelli et al, 2012; Carreras et al, 2005; Chen et al, 2017; Cirillo et al, 2004; Cronin et al, 2007; Dong et al, 2005, 2006; Fodi et al, 2013; Hamdan et al, 2009; Harbi et al, 2014; Hauser et al, 2006, 2015; Hof et al, 2009; Hoffmeister et al, 2007; Huang et al, 2018; Hunter et al, 2010; Ihara et al, 2011; Imanli et al, 2017; Istratoaie et al, 2019; Jongbloed et al, 2004; Jongbloed, Bax, et al, 2005; Jongbloed, Dirksen, et al, 2005; Kanaji et al, 2016; Kaseno et al, 2008; Klimek‐Piotrowska et al, 2016; Knecht et al, 2013; Koçyiğit et al, 2017; Krum et al, 2013; Kubala et al, 2011; Lickfett et al, 2004, 2005; Mansour et al, 2004; Martinez Urabayen et al, 2021; Merchant et al, 2016; Metzner et al, 2012; Micochova et al, 2005; Mulder et al, 2011; Niculescu et al, 2006; Patel et al, 2013; Pontone et al, 2015; Prasanna et a...…”
Section: Resultsmentioning
confidence: 99%